2007
DOI: 10.1111/j.1365-4632.2007.03210.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with 20% aminolevulinic acid for the treatment of recalcitrant viral warts in an Asian population

Abstract: 5-ALA-PDT, given its noninvasiveness, minimal adverse effects, and good cosmetic results, is a promising alternative treatment for recalcitrant viral warts. Further studies with a larger cohort of patients would be of value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…In regards to lesion type, Grapengiesser et al observed the most pain with AK, and the least with basal cell carcinomas (BCC), although differences in location and size of the treated areas for AK vs. BCC might confound these results 4 . Warts seem to generate considerable pain, significantly more in ALA-PDT treated warts as compared to placebo-PDT alone 20 ; the pain peaks as late as 24 hr and can persist up to 48 hr 21 . Acne vulgaris can be treated with light alone (without ALA) 22,23 , due to the fact that Proprionibacterium acnes produces and accumulates porphyrins within the sebaceous glands 24,25 .…”
Section: Factors Contributing To Pain Associated With Pdtmentioning
confidence: 99%
“…In regards to lesion type, Grapengiesser et al observed the most pain with AK, and the least with basal cell carcinomas (BCC), although differences in location and size of the treated areas for AK vs. BCC might confound these results 4 . Warts seem to generate considerable pain, significantly more in ALA-PDT treated warts as compared to placebo-PDT alone 20 ; the pain peaks as late as 24 hr and can persist up to 48 hr 21 . Acne vulgaris can be treated with light alone (without ALA) 22,23 , due to the fact that Proprionibacterium acnes produces and accumulates porphyrins within the sebaceous glands 24,25 .…”
Section: Factors Contributing To Pain Associated With Pdtmentioning
confidence: 99%
“…69 Cohort studies have reported clearance rates of warts between 58% and 95%. [70][71][72] PDT can be used in combination with laser; in such a study, 12 patients with periungual warts treated with CO 2 fractional laser followed by methyl-5-aminolaevuninic acid (MAL)-PDT (3 h, 50 J cm À2 , 15 min, fortnightly treatments over 6 weeks) resulted in 90% of treated warts clearing completely with no recurrence in 6 months. 73 In another study, 19 patients with hand and foot warts were treated with MAL-PDT plus a PDL light source, which cleared 53% of treated warts; hand warts cleared more effectively than plantar warts.…”
mentioning
confidence: 99%
“…This improvement was confirmed by a placebo-controlled study led by Bastuji-Garin et al [18]. In addition, Wang et al [19] successfully treated 42% of recalcitrant viral warts, and Chong and Kang [20] reported complete healing of recalcitrant foot verrucae vulgares after only 3 PDT sessions. Schroeter et al [21] treated periungual warts with full clinical success in 90% of patients after a mean of 4.7 sessions.…”
Section: Discussionmentioning
confidence: 77%